The Role of Artificial Intelligence Technology in Improving the Resilience of Supply Chain During COVID-19 - Zheng, Zhong; Zhang, Genge; Lin, Yun; Pan, Yanfang; He, Yandong (My University, 2022)
The outbreak of COVID-19 has posed continuous and huge challenges to the global supply chain. Difficulties in resuming work, border blockade, and sharp decline in market sales have increased the brittleness of the supply chain, which has put forward new and urgent demands on the resilience of the supply chain. In this context, this paper studies the impact of the epidemic on the supply chain, summarizes the thinking of enterprise representatives in typical industries on improving supply chain resilience under the epidemic situation, studies the specific strategies of using artificial intelligence technology to improve supply chain resilience, studies the correlation between supply chain resilience and artificial intelligence technology, analysis of artificial intelligence in improving supply chain resilience mechanism, specific analysis of artificial intelligence through what key technologies to improve supply chain resilience. On the basis, this paper construct artificial intelligence in the supply chain resilience technical framework, and construct a preliminary scheme for the integration of artificial intelligence and supply chain resilience, in order to provide for the outbreak to improve supply chain resilience reference and guiding significance.
Keywords: Artificial intelligence; COVID-19; Supply chain resilience